2022
DOI: 10.3390/diagnostics12112646
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in Liver Stiffness in Patients with Chronic Hepatitis B Undergoing Antiviral Therapy

Abstract: This is a retrospective single-center study that included 87 subjects. All subjects had chronic hepatitis B or HBV cirrhosis and underwent nucleos(t)ide analogs (NUC) treatment for more than one year. The study aimed to evaluate the dynamic changes in liver stiffness (LS) measured by transient elastography (TE) during a median interval of 64 months. Patients were assessed prior to starting therapy and followed up annually. Liver stiffness measurements (LSM) were performed annually, and ten valid LSMs were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
1
1
0
1
Order By: Relevance
“…Upon examining the HBV cohort, we observed a consistent increase in liver stiffness up to the point of intervention with treatment. This trend aligns well with existing literature on the subject [18,19].…”
Section: Discussionsupporting
confidence: 91%
“…Upon examining the HBV cohort, we observed a consistent increase in liver stiffness up to the point of intervention with treatment. This trend aligns well with existing literature on the subject [18,19].…”
Section: Discussionsupporting
confidence: 91%
“…Hasil penelitian oleh Erwi (r = 0,623, p < 0,01), menyatakan bahwa HBV DNA yang terdeteksi rendah memiliki korelasi yang kuat dengan sirosis (Erwi, 2021). Penelitian oleh Lazar et al, menemukan bahwa penderita hepatitis B kronik dengan pemeriksaan awal HBV DNA kadar rendah memiliki tingkat kekakuan hati yang lebih tinggi (Lazar et al, 2022). Namun, penelitian lain…”
Section: Metode Penelitianunclassified
“…The decrease in LS was greater in patients with initial cirrhosis after the first year and in patients with higher transaminase levels. In addition, HBV-DNA became undetectable in 90% of the population by the third year [ 62 ]. A study by our group also found a greater decrease in LS after treatment with NAs in patients with higher baseline values (−6 kPa in cirrhosis-advanced fibrosis with 14.1 KpA at baseline and −1.6 in nonadvanced fibrosis with 6.9 KpA at baseline) [ 63 ].…”
Section: Changes In Ls In Patients Undergoing Antiviral Therapymentioning
confidence: 99%